(untitled) (JONAH : Journal of Nursing and Homecare, 2025)
Primigravida mothers or mothers who are pregnant for the first time will experience physical and psychological changes so they will feel anxious and worried because this is a new experience. Anxiety has a bad impact on pregnant women because it can trigger stimulation of uterine contractions. One way to overcome anxiety is by applying positive affirmation relaxation techniques. The aim of this research is to describe the application of positive affirmation relaxation techniques to reduce the anxiety level of primigravida mothers in the working area of ​​the Payung Sekaki Community Health Center. This type of research is descriptive with 2 subjects conducted on April 23-27 2024. In this research data was collected by observation and presented in narrative and tabular form. The results of the study showed that the anxiety level of the two subjects before being given the intervention experienced severe anxiety and after applying the positive affirmation relaxation technique for 5 consecutive days in subjects I and II, it was found that the anxiety level had decreased. It is hoped that positive affirmation relaxation techniques can be applied in every health service in order to reduce the anxiety level of pregnant women.